2018
DOI: 10.1159/000495050
|View full text |Cite
|
Sign up to set email alerts
|

High Concentration of Aspirin Induces Apoptosis in Rat Tendon Stem Cells via Inhibition of the Wnt/β-Catenin Pathway

Abstract: Background/Aims: Non-steroidal anti-inflammatory drugs (NSAIDs) are commonly used in clinical practice to relieve fever and pain. Aspirin, as a representative NSAID, has been widely used in the treatment of tendinopathy. Some reports have demonstrated that aspirin can induce apoptosis in cancer cells. However, evidence regarding aspirin treatment for tendinopathy, especially the effect of this treatment on tendon stem cells (TSCs), is lacking. Understanding the effect of aspirin on tendinopathy may provide a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Celastrol exerts beneficial effects on human TSPCs stemness and the vital role of HIF1α-Smad7 signaling in the process is elucidated[47]. Celecoxib inhibits the tenogenic differentiation of TSPCs but has no effects on cell proliferation[48], and a high concentration of aspirin induces apoptosis in TSPCs by delaying the activation of Wnt/β-catenin pathway[49]. All these factors might affect the quality of tendon healing by targeting TSPCs, regardless of whether the effects are positive or negative.…”
Section: Tendon Stem/progenitor Cellsmentioning
confidence: 99%
“…Celastrol exerts beneficial effects on human TSPCs stemness and the vital role of HIF1α-Smad7 signaling in the process is elucidated[47]. Celecoxib inhibits the tenogenic differentiation of TSPCs but has no effects on cell proliferation[48], and a high concentration of aspirin induces apoptosis in TSPCs by delaying the activation of Wnt/β-catenin pathway[49]. All these factors might affect the quality of tendon healing by targeting TSPCs, regardless of whether the effects are positive or negative.…”
Section: Tendon Stem/progenitor Cellsmentioning
confidence: 99%
“…We performed the isolation and identification of rat TSCs as our previously studies . Briefly, rats in all groups were euthanized, and then, Achilles tendons were carefully collected.…”
Section: Methodsmentioning
confidence: 99%
“…We followed the methods as the previous studies. [12][13][14][15] Twentyfour male Sprague-Dawley rats were randomly divided into three groups: control group, injury model group and aspirin treatment group. Firstly, 30 μl collagenase I (10 mg/ml) were injected into both Achilles tendons of rats in injury group and aspirin treatment group to establish tendinopathy model.…”
Section: Animal Model Establishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the Wnt/β-catenin pathway played a vital role in aspirin-induced apoptosis by regulating mitochondrial/caspase-3 function. 22 Wang et al 23 found that inhibition of the Wnt/β-catenin signaling pathway improved the therapeutic effect on transcatheter arterial chemoembolization by suppressing migration and invasion while promoting the apoptosis of transplanted hepatocellular carcinoma cells in rats. Moreover, Rspo1 activated the Wnt/β-catenin signaling pathway, which is involved in the development, proliferation, and differentiation of stem cells, as well as the repair of tissue damage.…”
Section: Introductionmentioning
confidence: 99%